2015
DOI: 10.1090/proc/12587
|View full text |Cite
|
Sign up to set email alerts
|

The concordance classification of low crossing number knots

Abstract: We present the complete classification of the subgroup of the classical knot concordance group generated by knots with eight or fewer crossings. Proofs are presented in summary. We also describe extensions of this work to the case of nine crossing knots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Considerably less seems to be known with regards to finite order elements in ker ϕ. Kirk and Livingston showed that the knot 8 17 , which is negative-amphichiral, is not concordant to its reverse; hence 8 17 #8 r 17 represents a nontrivial element of order two in ker ϕ [26]; see also, [7]. In the present article, we extend this result by showing that there exists a subgroup H of ker ϕ such that H is isomorphic to (Z 2 ) 5 ; see Theorem 1.2 below.…”
Section: Introductionmentioning
confidence: 99%
“…Considerably less seems to be known with regards to finite order elements in ker ϕ. Kirk and Livingston showed that the knot 8 17 , which is negative-amphichiral, is not concordant to its reverse; hence 8 17 #8 r 17 represents a nontrivial element of order two in ker ϕ [26]; see also, [7]. In the present article, we extend this result by showing that there exists a subgroup H of ker ϕ such that H is isomorphic to (Z 2 ) 5 ; see Theorem 1.2 below.…”
Section: Introductionmentioning
confidence: 99%
“…and use it to provide another proof of the unboundedness of γ 4 by demonstrating that γ 4 (# n T (3,4) ) ≥ n, where # n T (3,4) is the n-fold connected sum of the (3, 4) torus knot T (3,4) with itself. The converse inequality γ 4 (# n T (3,4) ) ≤ n is easy to verify by finding an explicit Möbius band bounded by T (3,4) , leading to γ 4 (# n T (3,4) ) = n. γ 4 (K) = 1 for K = 9 1 , 9 3 , 9 4 , 9 5 , 9 6 , 9 7 , 9 8 , 9 9 , 9 13 , 9 15 , 9 17 , 9 19 , 9 21 , 9 22 , 9 23 , 9 25 , 9 26 , 9 27 , 9 28 , 9 29 , 9 31 , 9 32 , 9 35 , 9 36 , 9 41 , 9 42 , 9 43 , 9 44 , 9 45 , 9 46 , , 9 47 , 9 48 . γ 4 (K) = 2 for K = 9 2 , 9 10 , 9 11 , 9 12 , 9 14 , 9 16 , 9 18 , 9 20 , 9 24 , 9 30 , 9 33 , 9 34 , 9 37 , 9 38 , 9 39 , 9 40 , 9 49 .…”
Section: Introductionmentioning
confidence: 99%
“…Note that g top 4 (K) ≤ g 4 (K) ≤ g 3 (K). In another direction, Clark [3] defined the non-orientable 3-genus or 3-dimensional crosscap number γ 3 (K) as the smallest first Betti number of any non-orientable surface Σ ⊂ S 3 with ∂Σ = K. The non-orientable (smooth) 4-genus or 4-dimensional crosscap number γ 4 (K) was defined by Murakami and Yasuhara [20] as the minimal first Betti number of any non-orientable surface Σ smoothly and properly embedded in D 4 and with ∂Σ = K. Some authors additionally define γ 4 (K) = 0 for any slice knot K, but in the interest of a more unifying treatment we adopt the definition from the previous sentence. Just as in the case of oriented surfaces, so too for non-orientable surfaces there is a topological version of this invariant denoted by γ top 4 (K).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hedden-Kirk-Livingston have shown that there are many pairs of tight fibered knots (sums of algebraic knots) that are algebraically concordant and yet not topologically locally-flat concordant [HKL12]. Meier also points out that there are many pairs of positive non-fibered knots that are algebraically concordant and yet not topologically locally-flat concordant [Mei14]; as reported by KnotInfo and its Concordance Calculator, the positive knots 3 1 #9 2 and 9 23 give an example [CL14,CKL13].…”
mentioning
confidence: 99%